Population Genetic Analysis of the Threatened Plant Leavenworthia exigua var. laciniata (Brassicaceae) Reveals Virtually No Genetic Diversity and a Unique Mating System - Edwards, Christine E.; Bassüner, Burgund; Williams, Brigette R. (Frontiers in Conservation Science, 2022)
Leavenworthia (Brassicaeae) has served as a model group for investigating the evolution of mating systems in plants, yet several Leavenworthia species remain understudied. One such taxon is Leavenworthia exigua var. laciniata, one of three varieties of L. exigua, a winter-annual plant endemic to the central United States. Because L. exigua var. laciniata occupies a narrow geographic range and is experiencing major habitat loss, it was recently listed as threatened; however, little is known about its genetic diversity and implications for conservation. We conducted a rangewide population genetic study of L. exigua var. laciniata and L. exigua var. exigua to understand: 1) levels of genetic diversity within and among populations, 2) whether L. exigua var. laciniata is genetically distinct from L. exigua var. exigua, and 3) implications for conservation. L. exigua var. laciniata showed identical genotypes at all 16 microsatellite loci across most of its range, fixed heterozygosity at some loci, and significant heterozygote excesses, consistent with a lack of recombination associated with an asexual mating system, which has not been documented previously in Leavenworthia. Because L. exigua var. laciniata is an annual and the same genotype occurs across multiple populations, asexuality may be caused by apomixis, asexual reproduction via seed. In contrast, most populations of L. exigua var. exigua demonstrated population genetic patterns consistent with a self-compatible mating system. Because L. exigua var. laciniata is morphologically, geographically, and genetically distinct, it should be recognized as an evolutionarily significant unit for conservation. We recommend maintaining large population sizes to conserve evolutionary potential in L. exigua var. laciniata, as the likelihood that facultative sexual reproduction may occur may be greater in larger populations. Additional research in L. exigua var. laciniata is needed to confirm the occurrence of asexuality and apomixis, clarify its reproductive isolation from other taxa, and to understand whether it exhibits residual sexual reproduction, epigenetic variation, or phenotypic plasticity to help it persist in response to environmental variation. In the future, L. exigua var. laciniata may serve as an important model in which to investigate the conservation of threatened plant species with little genetic variation in a changing climate.